THE IRONY OF CONSOLATION IN EURIPIDES' PLAYS AND FRAGMENTS. (6th May 2016) - Chong-Gossard, James H. Kim On
Abstract : At the mid-point of Euripides' Hippolytus, Theseus arrives to find that his wife Phaedra has hanged herself, for a reason yet unknown. As he laments over his wife's corpse, the chorus of Troezenian women offers apparently standard consolation: